Wastewater reuse in coastal areas – Nutrient flow evaluation - Kathijotes, Nicholas (My University, 2011)
Weather changes and population increase on coastal zones clearly dictate higher demand for water which; in arid and semi arid regions is considered as a limited resource, with almost all groundwater resources under heavy pressure. Future demands will not be met by traditional water resources like surface and ground water. In order to handle increased water demand, the treated wastewater originating from municipal wastewater treatment plants has to be developed and offered to farmers for agricultural irrigation. Most of marine pollution arises from land-based activities such as urban development and sewage disposal, manufacturing, transport, energy production, and especially from tourism supporting agricultural activities. These inputs are a potential risk to ground water and the marine environment that need to be investigated. Nutrient effects on soils are then amplified, by investigating areas irrigated by wastewater and nearby sites irrigated with groundwater. Profile samples were taken in a field irrigated with treated wastewater, and in a nearby field irrigated with fresh farm water from the site for over ten years. All other variables like, crop types, irrigation modes and quantities, weather conditions were the same. Results suggest that, even though there is an increased nutrient input, no serious effects result through wastewater reuse and problems detected are manageable and may be handled with proper techniques. The aims of this investigation is to determine the distribution patterns of nutrients into the soil profile resulting from wastewater reuse .These nutrients eventually may end up into the groundwater creating quality degradation (eutrophication) of this resource as well as to the immediate marine environment. Results show an increase of nutrient values resulting from wastewater reuse at almost all experimental levels, but these increases are considered as manageable if proper care is exercised.
Keywords: Wastewater; Wastewater reuse; Total nitrogen; Nutrients; Phosphates